Assessment of fipronil toxicity on wistar rats: A hepatotoxic perspective. (2018) - Kartheek, R.M.; David, M.
Graphical abstract: Highlights: Fipronil was found to induce oxidative stress. Exposure to fipronil resulted in histopathology of hepatic tissue. Peak absorption changes in FT-IR was evident in liver of rats on Fipronil exposure. Fipronil modulated the enzymatic threshold of hepatic enzymes. Abstract: Extensive pesticide application has contributed to environmental contamination globally, imposing adverse health effects on non-target organisms. Need for an understanding of cellular response following pesticide exposure is, therefore, paradigmatic for elucidating perturbations occurring within biological systems. The present investigation was aimed to examine safe and toxic dose level of a persistent, synthetic, phenylpyrazole based insecticide, Fipronil (FPN) on rat liver. Experimental animals were divided into four groups and gavaged with 0.0 (control), 32.33 (high), 12.12 (medium) and 6.46 mg/kg body weight/day (low dose) of FPN for 90 days. While results for liver catalase and glutathione S -transferase indicated significant changes in high and medium dose groups, the superoxide dismutase and glutathione peroxidase activity suggested significant changes in all exposed groups as compared to control. Elevated levels of liver malondialdehyde reflected oxidative damage potential under the exposed groups but remained insignificant for low dose. Histologically, structural irregularities with findings like impaired portal vein and hypertrophy of hepatocytes were prominent under all the exposed groups. The FT-IR based spectral investigation further revealed changes in absorption patterns and peak intensities in rats exposed to FPN. Significant elevation was also noticed in liver enzymes; alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase in rat serum suggesting the toxicity in dose -dependent pattern. Based on the outcome, it could be ascertained that the toxicity of FPN is certain at high and medium dose levels but remains ambiguous at a low dose of 6.46 mg/kg body weight/day. The current upshots serve as a preliminary report thereby advising the farming community against the usage of FPN insecticide.